The effectiveness of a counseling program in reducing psychological stress among a sample of mothers of autistic children (مجلة جامعة سرت للعلوم الانسانية, 2023)
The current study aimed to provide a counseling program to reduce psychological stress in a sample of mothers of children with autism disorder. The study sample consisted of (20) mothers, whose children suffer from autism disorder. She has the counseling program and the other is a control one, she was not subject to the counseling program, and the study tools consisted of a measure of psychological stress and the counseling program, and the results of the study found that there were differences between the experimental and control groups in the post-measurement in favor of the experimental group, which confirms that the counseling program has its effectiveness in reducing psychological stress .
Keywords: Children; Autism